Filing a Lawsuit for Damages in Enforcing the Civil Aspects of Business Competition - Sanusi Sanusi; Bha’iq Roza Rakhmatullah (Faculty of Law, Universitas Jenderal Soedirman, 2022)
In the life of society, the law has a main objective, which is to regulate the life of society and the state in all its activities. Various community activities include social, political, and cultural activities. It is hoped that the activities carried out by the community, especially in trade, will not exceed the limits of the provisions implied in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The purpose of this study is to analyze the business competition system in Indonesia against a business actor who is disadvantaged as a result of unfair business competition practices, whether he can file a claim for rights or a lawsuit in the form of payment of compensation through civil law enforcement procedures without first reporting in writing the occurrence of the practice to Commission for the Supervision of Business Competition (KPPU). This type of research uses library materials as secondary data and laws and regulations as a system of norms that must be obeyed and by usingan approach philosophical. Business actors who have been harmed based on Article 1365 of the Civil Code as the basis for the right to tort or Article 1239 of the Civil Code as the basis for the right to default can file a lawsuit directly to the District Court without first reporting in writing to the Business Competition Supervisory Commission (KPPU). KPPU as an institution responsible for implementing business competition law enforcement is a complementary state institution (state auxiliary organ) regardless of government influence. In practice, KPPU is an institutionas if judicial because the KPPU has the same authority as the judiciary, one of which is the authority to issue decisions and decisions.Keywords: Lawsuits, Compensation, Unfair Business Competition